2013
DOI: 10.1155/2013/487695
|View full text |Cite
|
Sign up to set email alerts
|

Lisbon Urban Heat Island Updated: New Highlights about the Relationships between Thermal Patterns and Wind Regimes

Abstract: Urban growth implies significant modifications in the urban climate. To understand the influence of the city of Lisbon on the urban boundary layer, a mesoscale meteorological network was installed in 2004. The main goals of the present study are to update the results of the research published in 2007 and to bring more precise information about the relationship between the Urban Heat Island (UHI) and the regional and local wind systems. The highest frequencies of the UHI were found in the city centre (Restaurad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
2
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 22 publications
(45 reference statements)
5
67
2
22
Order By: Relevance
“…7). Data source: CliMa-CeG-ULisboa the relationship between UHii and wind has been studied and verified recently by Lopes et al (2013). the plots of UHii versus wind speed show an expected reduction of UHi intensity when wind exceeds 4 m/s ( fig.…”
Section: Fig 5 -Blox Plots Da Intensidade Da Ilha De Calor Diurna (1mentioning
confidence: 69%
See 2 more Smart Citations
“…7). Data source: CliMa-CeG-ULisboa the relationship between UHii and wind has been studied and verified recently by Lopes et al (2013). the plots of UHii versus wind speed show an expected reduction of UHi intensity when wind exceeds 4 m/s ( fig.…”
Section: Fig 5 -Blox Plots Da Intensidade Da Ilha De Calor Diurna (1mentioning
confidence: 69%
“…One very interesting feature in figure 7 is the fact that, in summer, high UHii begins quite early in the afternoon, which can be explained by the wind regime in the city (alcoforado, 1987;Lopes et al, 2013). in the summer mornings, there are frequently e and se breezes from the tagus estuary that veer to the s and sW by midday or later, bringing cooler air into the river-site city centre, sometimes up to res (andrade, 2003) and in summer cause a negative heat island from 9:00h to 12:00h (or later).…”
Section: Fig 5 -Blox Plots Da Intensidade Da Ilha De Calor Diurna (1mentioning
confidence: 99%
See 1 more Smart Citation
“…To reach the ∆Tu (group) -r (group) of the UHI, we need to minimize the microclimatic influences of each station so that the local influence prevails. Some studies have used a group of stations to calculate UHI intensity instead of using only one station that represents the urban area and another that represents the rural area [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…By using daily data between 1972 and 1991, Morris et al [5] showed, among other results, that the variation in the amount of clouds from 0 to 8 octas had very little influence on Melbourne UHI when the mean wind was ≥5 ms −1 . By using daily data between 2004 and 2012, Lopes et al [3] and Alcoforado et al [4] reported that low wind speeds were not associated with the highest Lisbon UHI intensities. In Aracaju, using the approaches discussed above, some studies pointed to higher heating in the central areas (up to 7.5 • C) in relation to the peri-urban areas and green spaces, which suggests that UHI intensities are equally significant [10][11][12].…”
Section: Introductionmentioning
confidence: 99%